The Use of YouTube as a Supplementary Resource in Students' Speaking Skills - Resti Farikhah Zulaefa; Daviq Rizal (Universitas Ahmad Dahlan, 2023)
This study aimed to investigate the use of YouTube videos as a supplementary resource for EFL students. It uses a descriptive qualitative research method. The sample in this study was ten students in senior high school who had experienced learning EFL through YouTube as a supplementary resource for speaking fluency. The data collection instrument is a google form questionnaire with open-ended and close-ended questions. According to the findings, using YouTube in EFL classes positively supports speaking fluency for EFL learners, particularly in shaping and organizing ideas, enhancing motivation, developing and supporting peer collaboration, improving vocabulary, and reducing students' shyness. The current study's findings have clear implications for the teacher and students on how the students utilize YouTube as a supplementary resource in increasing their speaking fluency; the resource should focus more on developing student speaking fluency.